Adherence of Vibrio parahaemolyticus to human epithelial cell lines. - Gingras, S P (1980)
Light microscopy and a radioassay detected no significant difference in adherence of Kanagawa-positive and Kanagawa-negative strains of Vibrio parahaemolyticus to human epithelial cell lines.